Presents or investments? An experimental analysis - Uri Gneezy; Werner Güth; Frank Verboven (Humboldt University of Berlin, Interdisciplinary Research Project 373: Quantification and Simulation of Economic Processes, 1998)
Individuals frequently transfer commodities without an explicit contract or an implicit enforcement mechanism. We design an experiment to study whether such commodity transfers can be viewed as investments based on trust and reciprocity, or whether they rather resemble presents with distributional intentions. Our experiment essentially modifies Berg et al.'s investment game by introducing an upper bound to what a contributor can be repaid afterwards. By varying this upper bound, extreme situations such as unrestricted repayment and no repayment (dictator giving) can be approximated without altering the verbal instructions otherwise. Our results show that individuals contribute more when large repayments are feasible. This is consistent with the trust and reciprocity hypothesis. Although distributional concerns in some contributions can be traced, they are not nearly close to a preference for equal payoffs.
urn:nbn:de:kobv:11-10057090
Keywords: 330